Cyberchondria and Adolescent Mental Health: School Counseling Interventions - Hidayatullah, Hengki Tri; Setiyowati, Arbin Janu; Ramli, M.; Wahyuni, Fitri (Bisma The Journal of Counseling, 2025)
The increasing use of the internet as a source of health information has given rise to the phenomenon of cyberchondria, characterized by excessive health information-seeking behavior that negatively impacts adolescent mental health. This phenomenon has become increasingly concerning, especially in the post-pandemic era, where health anxiety and exposure to unverified information have risen significantly. This study aims to analyze the psychological impact of cyberchondria on adolescents and to evaluate the role of school counseling services in preventing and managing its symptoms. The research employed a Systematic Literature Review method, guided by the PRISMA 2020 protocol. A total of 19 international articles published between 2013 and 2024 were analyzed, focusing on adolescents aged 12–18 years, with a combined sample of over 21,000 participants. Data were collected using a structured extraction form and analyzed thematically. The findings indicate that cyberchondria is closely associated with anxiety, family dysfunction, smartphone addiction, and a decline in psychological well-being. School-based counseling holds strategic potential in fostering digital health literacy and reducing maladaptive health information-seeking behaviors. Overall, these results highlight the need for a systemic approach within the education sector to address emerging adolescent mental health challenges driven by uncontrolled digital information consumption.